University Support and Its Influence on the Entrepreneurial Intentions of East Java Students: Mediation of Entrepreneurial Mindset - Subroto, Agus Andi; Anwar, Khoirul; Sari, Dina Fahma (Jurnal Aplikasi Manajemen, 2025)
The high unemployment rate among university graduates in Indonesia underscores the urgent need for universities to encourage students to become job creators. However, most previous studies have focused more on individual factors such as motivation, personality, or self-efficacy in relation to entrepreneurial intent, while the role of institutional support from universities and the process of internalizing an entrepreneurial mindset have rarely been studied comprehensively, especially in the context of private universities in East Java, which are characterized by an MSME-based economy and high graduate unemployment rates. The study aims to analyze the effect of university support on students’ entrepreneurial intentions, with entrepreneurial mindset as a mediating variable, and gender and training participation as moderators. This study uses a quantitative approach with a survey method. This study population consists of private university students in East Java, with a total of 400 respondents selected through purposive sampling. The questionnaire instrument was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that university support significantly influences entrepreneurial intention both directly and indirectly through entrepreneurial mindset. Multi-group analysis revealed that the effect of university support was stronger among female students and those who participated in entrepreneurship training. The findings highlight that campus-based support systems in the form of curriculum, training, mentoring, and business incubation can strengthen students' entrepreneurial mindset so that they are more creative, innovative, and dare to take risks in starting a business. The study’s novelty lies in integrating institutional and psychological factors within a single comprehensive model, specifically contextualized to East Java’s socio-economic dynamics. Theoretically, it extends the Theory of Planned Behavior by emphasizing the mediating role of the entrepreneurial mindset. In practice, it provides universities with a foundation for designing inclusive, gender-responsive, and experience-based entrepreneurship programs to reduce graduate unemployment.